FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEREMPUAN BEKERJA PADA SEKTOR INFORMAL DI DESA BANJAR ANYAR KABUPATEN TABANAN - Ayu Cahayani, Made Shinta Devi; Purwanti, Putu Ayu Pramitha (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2019)
The purpose of this study was to study the factors that influence the income of women working in the informal sector. This research was conducted in Banjar Anyar Village, Tabanan Regency. The sample in this study were 92 people. The analysis technique of this research is multiple linear regression analysis. Age variables, number of household members, education, working hours and social capital significantly influence the income of women in the informal sector in Banjar Anyar Village, Tabanan Regency. Educational variables, number of household members, and hours of work, partial work, positive, and significant income for women, work in the informal sector in Banjar Anyar Village, Tabanan Regency, while age and social capital variables are not related to female labor in the informal sector in Banjar Anyar Village, Tabanan Regency.